CHANGES TO THE REGIONAL MEDIUM-TERM DEVELOPMENT PLAN DURING THE COVID-19 PANDEMIC PERIOD IN THE LEGAL PERSPECTIVE OF REGIONAL GOVERNMENT - Boemiya, Helmy (Faculty of Law Universitas Trunojoyo Madura, 2023)
Provincial Government, Regencies and cities in the context of administering their administration must prepare development plans. However, there is a main problem, namely the Covid-19 pandemic since March 2020 until now, which has greatly affected the national economy. The purpose of this study is to find out the arrangements for changing the Regional Medium-Term Development Plan (RPJMD) during the Covid-19 pandemic and the changes that must be made or become a priority in preparing the RPJMD Changes. The research method used is normative juridical. Changes to the RPJMD during the Covid-19 pandemic have a legal basis, namely first, local governments have the authority through local regulations to amend the RPJMD, second, regulations related to Law No. 23 of 2014, Government Regulation No. 8 of 2008, Presidential Regulation No. 18 of 2020, Minister of Home Affairs Regulation No. 86 of 2017 allows the RPJMD to be changed on the basis of a fundamental change in national policy and the existence of a non-natural national disaster. third, in making changes to the RPJMD according to Government Regulation No. 86 of 2017 and Minister of Home Affairs Regulation No. 70 of 2019. In preparing changes to the RPJMD, the local government must pay attention to the philosophical basis, namely that Indonesia has a national philosophy, namely Pancasila. Then the sociological basis for changing the RPJMD is the involvement of the community in a policy formulation process which is a concrete manifestation of the application of modern democratization values.